The finalists - Bell, David, 1969 November 17- (Berkley, 2022)
On a beautiful spring day, six college students with nothing in common besides a desperate inability to pay for school gather to compete for the prestigious Hyde Fellowship. Milo--The front-runner. Natalia--The brain. James--The rule follower. Sydney--The athlete. Duffy--The cowboy. Emily--The social justice warrior. The six of them must surrender their devices when they enter Hyde House, an aging Victorian structure that sits in a secluded part of campus. Once inside, the doors lock behind them. The students are not allowed to leave until they spend eight hours with a college administrator who will do almost anything to keep the school afloat, and Nicholas Hyde, the privileged and notoriously irresponsible heir to the Hyde family fortune. If the students leave before time is up, they'll be immediately disqualified. But when one of the six finalists drops dead, the other students fear they're being picked off one by one. With a violent protest raging outside, and no way to escape, the survivors viciously turn on each other.--